Néel State in the Fermionized Spin 1/2 Heisenberg Antiferromagnet on Hypercubic and Triangular Lattices - Thang, Nguyen Toan; Nga, Pham Thi Thanh (Communications in Physics, 2012)
We study the Néel state of the spin 1/2 Heisenberg antiferromagnet model on hypercubic and triangular lattices, employing an auxiliary fermion representation for spin operators with Popov-Fedotov trick. The unphysical states are eliminated on each site by introducing an imaginary chemical potential. Working in local coordinate systems we obtain the free energy and the sublattice magnetization for both lattices in an unified manner. We show that exact treatment of the single occupancy constraint gives a significant effect at finite temperatures